Racial differences in human platelet PAR4 reactivity reflect expression of PCTP and miR-376c - Edelstein, Leonard C; Simon, Lukas M; Montoya, Raúl Teruel; Holinstat, Michael; Chen, Edward S; Bergeron, Angela; Kong, Xianguo; Nagalla, Srikanth; Mohandas, Narla; Cohen, David E; Dong, Jing-fei; Shaw, Chad; et al. (Nature medicine, 2013)
In exploring the possibility that racial differences in platelet function might exist, Paul Bray and his colleagues report that platelets from blacks have a greater propensity to aggregate than those from whites in response to activation of the PAR4 thrombin receptor. Mechanistically, this difference in platelet function seems to reflect differences in the expression of the microRNA miR-376c and its target, the enzyme phosphatidylcholine transfer protein. Racial differences in the pathophysiology of atherothrombosis are poorly understood. We explored the function and transcriptome of platelets in healthy black ( n = 70) and white ( n = 84) subjects. Platelet aggregation and calcium mobilization induced by the PAR4 thrombin receptor were significantly greater in black subjects. Numerous differentially expressed RNAs were associated with both race and PAR4 reactivity, including PCTP (encoding phosphatidylcholine transfer protein), and platelets from black subjects expressed higher levels of PC-TP protein. PC-TP inhibition or depletion blocked PAR4- but not PAR1-mediated activation of platelets and megakaryocytic cell lines. miR-376c levels were differentially expressed by race and PAR4 reactivity and were inversely correlated with PCTP mRNA levels, PC-TP protein levels and PAR4 reactivity. miR-376c regulated the expression of PC-TP in human megakaryocytes. A disproportionately high number of microRNAs that were differentially expressed by race and PAR4 reactivity, including miR-376c , are encoded in the DLK1-DIO3 locus and were expressed at lower levels in platelets from black subjects. These results suggest that PC-TP contributes to the racial difference in PAR4-mediated platelet activation, indicate a genomic contribution to platelet function that differs by race and emphasize a need to consider the effects of race when developing anti-thrombotic drugs.